SMEs barriers and enablers to challenge foreign countries - Pereira, L.; Bessa, F.; Dias, Á.; Gonçalves, R.; Lopes da Costa, R. (International Journal of Globalisation and Small Business, 2022)
Due to globalisation, countries, businesses, and people from different nations have become more interconnected than ever before in recent years. Following this trend, there is a growing indication for the rising engagement of SMEs in international marketplaces. When beginning the internationalisation process, larger firms can deal more effectively with barriers than SMEs. This study focused on the external barriers, drivers, support, incentives, and protection from public domestic organisations and institutions dedicated to SME internationalisation. After 20 interviews conducted with professionals with high positions in various organisations in the internationalisation ecosystem, the results suggest that public support for SMEs is essential for the companies to survive and succeed in the foreign markets.